Analisis Perencanaan Kehamilan dan Persalinan di Lingkungan Parang Banoa Kelurahan Parang Banoa Kecamatan Pallangga Kabupaten Gowa - Sitti Patimah; Nurgahayu Nurgahayu; Nurul Faimah; Nurul Fairah; Elis Elis; Anugrah Aulia Putri; Nur Arian Dini (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Pregnancy planning is an important factor in ensuring maternal and fetal health during pregnancy and reducing the risk of complications that can lead to maternal and infant mortality. This study aims to describe the level of public awareness in the Parang Banoa Environment, Parang Banoa Village, Pallangga District, Gowa Regency, regarding safe pregnancy and childbirth planning. The research method used is quantitative with a descriptive approach, data collection techniques in the form of questionnaires processed using the SPSS application. Respondents in this study consisted of 23 families who had pregnant women. The results showed that most respondents, namely 86.9%, planned their pregnancies well, which indicates a high level of awareness of the importance of pregnancy planning. In addition, 86.9% of pregnant women also planned to save for childbirth costs, indicating their financial readiness. However, awareness of planning prospective blood donors is still low, with only 43.5% of respondents planning prospective blood donors during childbirth. The results of the study showed that 100% of respondents had planned transportation for childbirth, with the majority choosing an ambulance or mobile health center car as a means of transportation. In terms of birth attendants, most respondents (73.91%) chose doctors as their birth attendants. Based on these findings, it is recommended that public education be increased regarding planning for prospective blood donors, financial literacy to save on birth costs, and choosing safe transportation. In addition, it is important to continue to strengthen understanding of the importance of choosing competent medical personnel as birth attendants to ensure the safety of the mother and baby during the birth process.